A Machine Learning Approach for Prediction of Gibberellic Acid Metabolic Enzymes in Monocotyledonous Plants. (2014) - S, Sreepriya P. Naganeeswaran; N, Hemalatha; P, Sreejisha; K, Rajesh M.
No abstract available